(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The term mobile commerce was first used in 1997 by Kevin Duffey to announce the GlobalMobile Commerce Forum. In India, more consumers are switching to mobile commerce to achieve betterand faster transactions thanks to the applications’ impressive growth. The mobile telecom market hasexperienced significant growth quick changes in recent years both internationally and in India.Chennai city was chosen as the subject of the descriptive research. A research was carried out amongrespondents from three different regions of Chennai, spanning a range of ages professions, in order tovalidate the questionnaire. The necessary data is gathered using the purposive sampling method. Therandom sample approach is then used to collect various demographic occupational data after thesefirst two steps. A thorough questionnaire with 702 variables was used to gather the data. The study usedthe t-test. The respondents believe that using mobile commerce applications requires quickness.